2009
DOI: 10.1103/physreve.80.056212
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical thermalization of disordered nonlinear lattices

Abstract: We study numerically how the energy spreads over a finite disordered nonlinear one-dimensional lattice, where all linear modes are exponentially localized by disorder. We establish emergence of dynamical thermalization, characterized as an ergodic chaotic dynamical state with a Gibbs distribution over the modes. Our results show that the fraction of thermalizing modes is finite and grows with the nonlinearity strength.PACS numbers: 05.45.-a, 63.50.-x, 63.70.+h The studies of ergodicity and dynamical thermal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 32 publications
3
80
0
Order By: Relevance
“…This feature has been noted and used for nonlinear chains with disorder [31,32] and Bose-Einstein condensates, described by the GrossPitaivskii equation, in chaotic two-dimensional billiards [33]. It is interesting to note that in these nonlinear systems [31][32][33] the DTC is still valid but it is induced by a nonlinear mean-field interactions between linear states. (12) where β and µ were chosen such that k n k = N = 8 and k E k n k + N 2 U/L = Eα with Eα/N corresponding to the centers of the abscissa intervals (e.g.…”
Section: Numerical Resultsmentioning
confidence: 96%
“…This feature has been noted and used for nonlinear chains with disorder [31,32] and Bose-Einstein condensates, described by the GrossPitaivskii equation, in chaotic two-dimensional billiards [33]. It is interesting to note that in these nonlinear systems [31][32][33] the DTC is still valid but it is induced by a nonlinear mean-field interactions between linear states. (12) where β and µ were chosen such that k n k = N = 8 and k E k n k + N 2 U/L = Eα with Eα/N corresponding to the centers of the abscissa intervals (e.g.…”
Section: Numerical Resultsmentioning
confidence: 96%
“…n = σ /2 + 1 corresponds to n-body interactions, and σ = 1 relates to quadratic Kerr media in nonlinear optics. Mulansky [55] presented numerical simulations of the gDNLS model for a few integer values of σ and single site excitations, and fitted the dependence m 2 (t) ∼ t α with exponents α which depend on σ (see open circle data in left plot in Fig.10). In [56] numerical simulations of the gDNLS model were performed for non integer values of σ on rather short time scales, leaving the characteristics of the asymptotic (t → ∞) evolution of wave packets aside.…”
Section: Tuning the Power Of Nonlinearity And The Lattice Dimensionmentioning
confidence: 99%
“…In this case, due to Anderson localization, linear eigenmodes are exponentially localized and the spectrum is purely discrete [4]. Recent numerical experiments with nonlinear disordered lattices have demonstrated that the initially localized wave packets spread in a very weak, subdiffusive manner [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. A complete theoretical understanding of the subdiffusive behavior has not been presented, but it is mostly agreed that the spreading in these models is induced by weak chaos.…”
Section: Introductionmentioning
confidence: 99%